Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Bimbingan Belajar LPR - Siti Mabrur Rachmah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The purpose of this study is to analyze the effect of service quality on customer satisfaction at LPR Course. This research adopts a quantitative approach, utilizing primary data collected from customers or students of the LPR Course as the sample. The data were gathered using a saturation sampling technique, involving 20 respondents. The study employs simple regression analysis to examine the relationship between service quality and customer satisfaction. The findings reveal that service quality has a significant and positive effect on customer satisfaction at LPR Course.